2007
DOI: 10.1038/sj.mt.6300241
|View full text |Cite
|
Sign up to set email alerts
|

Successful Immunization with a Single Injection of Non-integrating Lentiviral Vector

Abstract: We evaluated the ability of an integrase (IN)-defective self-inactivating lentiviral vector (sinLV) for the delivery of human immunodeficiency virus-1 (HIV-1) envelope sequences in mice to elicit specific immune responses. BALB/c mice were immunized with a single intramuscular injection of the IN-defective sinLV expressing the codon optimized HIV-1(JR-FL) gp120 sequence, and results were compared with those for the IN-competent counterpart. The IN-defective sinLV elicited specific and long-lasting immune respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
123
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(144 citation statements)
references
References 44 publications
20
123
0
Order By: Relevance
“…22,51 Observations that an IDLV generated reduced humoral immune responses may also indicate reduced protein expression. 54 The results from our laboratory indicate that FIV IDLV luciferase reporter transgene expression is B10-fold less than a matched integrating FIV LV control (MB Banasik and PB McCray, unpublished observation).…”
Section: Idlv Biologymentioning
confidence: 99%
See 3 more Smart Citations
“…22,51 Observations that an IDLV generated reduced humoral immune responses may also indicate reduced protein expression. 54 The results from our laboratory indicate that FIV IDLV luciferase reporter transgene expression is B10-fold less than a matched integrating FIV LV control (MB Banasik and PB McCray, unpublished observation).…”
Section: Idlv Biologymentioning
confidence: 99%
“…[47][48][49] Several reports have detailed the production of HIV IDLVs. 13,22,44,[47][48][49][50][51][52][53][54][55][56][57][58][59][60] In addition, feline immunodeficiency virus (FIV) IDLVs are also described. 48 Integrase-defective LVs: progress and applications MB Banasik and PB McCray Jr studies ( Figure 1).…”
Section: Integrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Since DCs (the most potent Ag presenting cells) are non-dividing, it is likely that non-integrating lentivector will be equally effective in stimulating Ag specific immune responses. Indeed, Negri et al showed that single immunization with non-integrating lentivector stimulate potent and persistent T cell responses and antibody production at day 30 and day 90 comparable to that induced by integrated lentivector although they did not examine if effector function early time points was similar 37 .…”
Section: Lentivector Developmentmentioning
confidence: 99%